KEMAMPUAN MAHASISWA DALAM MEMAHAMI BACAAN PADA BUKU TEKS MATEMATIKA BERBAHASA INGGRIS - Rohmah Indahwati; Evha Nazalatus Sa'adiyah (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
English Mathematics course mostly deals with comprehension questions, grammar and vocabulary related to the field of Mathematics. The goal is that students have the confidence in communicating using English as well as utilize various sources of English teaching materials. But in reality, they usually experience several problems as the medium of instruction changes from their mother tongue to another language. This phenomenon in the case of Mathematics education brings the consequences faced by Mathematics educators. This paper describes the understanding of Mathematical concepts in English textbooks (Fraction) on the students of English Mathematics Study Course of Mathematics Education of Madura University. The data that used in this research is the result of the translation scripts of students at the Mathematics education department on the fractional concepts in English textbooks, observations on the student presentation and interviews. The result of this research are, Subjects still have not been able to understand the meaning of fractions that are linked in real objects and clear Mathematical models, subjects still used word-for-word translation, translating without providing meaningful information and also lack of vocabulary.